Penerapan Six Sigma untuk Peningkatan Kualitas Jasa Layanan IndiHome - Irnanda Pratiwi; Faizah Suryani; M. Reza Adrian (Universitas Teuku Umar, 2021)
The development of the broadband internet access business is getting tighter these days, encouraging companies to prioritize service quality to achieve predetermined goals and objectives. IndiHome service is one of the internet access services from PT Telekomunikasi Indonesia whose access network is managed by PT Telkom Akses. PT Telkom Akses is Telkom's commitment to continue to develop unlimited broadband networks for all Indonesian people. Based on the data, there are 10.751 IndiHome services that are disrupted, with the results of the analysis using the Six Sigma method, it is known that the sigma level is 3.90 with the possibility of service being interrupted by 8,696 in a million possibilities, there are three potential Critical to Quality potentials, namely Disconnected Outdoor Cables (47,29%), Defective Splitters (31,84%), and Home Cable Installation (20,87%).